STRATEGI MANAJEMEN PORTOFOLIO OBLIGASI - , MALIM MUHAMMAD, S.Si, Dr. rer.nat. Dedi Rosadi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The duration of an instrument to measure the level of a bond's price sensitivity to change in interest rate or changes in bond yields. Bond duration is the number of years needed to be able to return the purchase price of bonds. Convexity is a measure of curvature of bond curve showing the relationship between price and convexity method will produce more accurate count in calculate the price of bonds that experience changes in interest rate. Active portfolio management is a way in which the investment manager to provide an overview of the situation that will occur in the future. Thus, the investment manager can predict the interest rate a future time by observing the movement on interest rate sensitive bond price and total return portfolio.